2020
DOI: 10.1109/ojcoms.2020.3007171
|View full text |Cite
|
Sign up to set email alerts
|

A Wideband Spectrum Sensing Approach for Cognitive Radios Based on Cepstral Analysis

Abstract: Multiband spectrum access plays an essential role in cognitive radio systems so as to increase the network's throughput through wideband spectrum sensing. It includes identifying the number of subbands comprising a wide spectrum by edge detection, and also examining their occupancy through primary user detection techniques. Despite the offered accuracy of the wavelet-based approaches, their complexity becomes a drawback. Remarkably, the features revealing property of cepstral analysis and its implementation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To address the issue of spectrum scarcity, [Moawad et al, 2020] suggested a wideband spectrum detection method based on cepstral analysis. To begin, they proposed an adaptive log-spectral density technique for the edge determination phase, detecting spectral limits.…”
Section: Cyclostationary Detectionmentioning
confidence: 99%
“…To address the issue of spectrum scarcity, [Moawad et al, 2020] suggested a wideband spectrum detection method based on cepstral analysis. To begin, they proposed an adaptive log-spectral density technique for the edge determination phase, detecting spectral limits.…”
Section: Cyclostationary Detectionmentioning
confidence: 99%
“…In this regard, SS that focuses on one narrow channel, such as ED and CSD, may not be sufficient. Instead, Wide Band Sensing (WBS) [ 181 , 182 , 183 ], which is able to explore a wide frequency band, will be a good candidate to meet the frequency needs of the CR network. From the CR point of view, WBS ensures a high data rate for the SUs since the data rate is directly related to the bandwidth.…”
Section: Cognitive Radio Application For 5g and Beyond 5gmentioning
confidence: 99%